PELATIHAN ENGLISH STORY-TELLING PADA SISWA-SISWI SMP MUHAMMADIYAH PANGKALPIINANG BERBASIS HAYATUS-SAHABAH - Redika Cindra Reranta; Rifki Hanif Setiawan; Tiara Putri Safira; Kurnia Akbar (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The aim of this research is to improve the public speaking skills of Muhammadiyah Pangkal Pinang Middle School students through English storytelling training based on Hayatus Sahabah. This program uses the life stories of the companions of the Prophet Muhammad SAW. As the main teaching material to train cultural students in English. This approach combines English language learning with Islamic values ​​not only to improve language skills students, but also to strengthen their enthusiasm and self-confidence. The method used is intensive participatory training which includes the stages of providing material, developing teaching stories, implementation practices and evaluation. The training lasted for six meetings and involved students selected through competitive examinations. Data was collected through observation and interviews. Data analysis shows that this training has had a positive impact on improving students' skills in story structure, pronunciation, fluency and clarity of delivery. This research shows that students' public speaking scores increased by an average of 30% compared to before training. In addition, students reported increased motivation, increased self-confidence, and a deeper understanding of the inspiring stories of the prophet's companions. This approach also encourages students to practically integrate language skills based on Islamic values ​​in everyday life. Therefore, this training can be an effective method for developing public speaking skills while strengthening Islamic character values ​​in students.